The World War II book - Gilbert, Adrian; Adams, Simon, 1955-; Farndon, John; Field, Jacob F.; Grant, R. G.; Levy, Joel, 1971-; Smith, Olivia (Public historian); Westhorp, Christopher (Big ideas simply explained., 2022)
"Discover the key battles, tactics, technologies, and turning points of the Second World War - the epic conflict that shaped the modern world. Combining authoritative, exciting text and bold explanatory graphics, The World War II Book explores the causes, key events, and lasting consequences of the Second World War. Using the original, graphic-led approach of the series, entries profile more than 90 of the key ideas and events during and surrounding the conflict - from the rise of Hitler and Fascism in the 1930s to Pearl Harbor, the D-Day landings, and the bombing of Hiroshima to the founding of the State of Israel in 1948. Offering a uniquely compelling, accessible, and immediate history of the war, The World War II Book shows how key battles, political and economic forces, individual leaders, and technological advances influenced the course of the conflict."--Amazon.com.